Social media : to embrace or to contain? - Ng, Hon Kuan. (2013)
Social media, the main organising platform of social movements since 2008, have presented various dilemmas to the states throughout the world. This thesis attempts to unpack these dilemmas and examine the impact of social media on Westphalian conceptions such as sovereignty and identity of sovereign-state and citizen. This paper also examines how nation-states react to the implications. The paper traces six social movements that span ten years in time and five continents geographically to showcase how each event inherits lessons from the former one. They disrupt the established hierarchical order, and render national borders and sovereignty obsolete. In the process, they present citizen and sovereign-state the opportunities of rearticulating the their identities, relations between them and between citizens of different nationalities. The emergence of print-capitalism had contributed to the budding of national consciousness, the paper therefore foresees a brewing slate of new imagined communities that will change the status quo of sovereign-states and transnational relations, on the one hand; and partitions people along the line of common beliefs, shared values or simply informational ‘haves’ and ‘have-nots’, on the other hand.